Pelatihan Penerapan GMP Pembuatan Dodol Rumput di Desa Kedung Pandan Kecamatan Jabon - budiandari, rahmah utami; Hudi, Lukman; Prihatiningrum, Andriani Eko; Sahara, Zhahlya Amaldha (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2024)
Purpose – The purpose of this activity is to provide knowledge and skill of Kedung Pandan Village;s people in optimizing the diversification of seaweed processed product into Dodol. Design/methodology/approach – The implement methods includes presentation, discussions, training and mentoring programs including training on the process of making dodol and applicaton of GMP, an evaluation stage Findings – Training activities are conducted by producing outpus such as seaweed porridge processing techniques, packaged dodol products. The evaluation results show the high desire of Kedung pandan village’s people to develop seaweed, that easy to find but innovation and creation are still needed so the product can become icon of Desa Wisata Bahari Tlocor Originality/Value – Through this community service, we can diversify seaweed, add value added of seaweed and created a snack icon for the Desa Wisata Bahari Tlocor